Cradles of industry and occupational medicine in the modern world: Milan 1906 - Annus Mirabilis / Culle dell’industria e della medicina del lavoro nel mondo moderno: Milano 1906 - Annus Mirabilis - Baldasseroni, Alberto; Carnevale, F.; Tomassini, L. (La Medicina del Lavoro, 2012)
Background: The example examined is Milan, Italy’s main industrial city, where the great International Exhibition was held in 1906. This was the culmination of a period of accelerated industrial growth that modern-day historiography considers to be when Italy’s first real industrial revolution began. The twenty-five years between the National Industrial Exhibition of 1881, which was also held in Milan, and the 1906 Exhibition truly reflected a period which was crucial for this transformation to take off. Alongside industry, which was then going through a phase of reorganization and development, Milanese civil society was increasingly turning its interest and attention to what was called the “Social Question”. In an atmosphere of debate and exchange of ideas and experience with Turin, another major industrial city of the north and the birthplace of the Italian engineering and automobile industries, social organizations, political parties and trade unions began to be established thus heralding the Italian approach towards twentieth-century welfare. Results: This is the context in which the first International Congress on Occupational Diseases was held in Milan from 9 to 14 June 1906 within the framework of the International Exhibition. The success achieved with this initiative. organized by Luigi Devoto and Malachia De Cristoforis, which was to continue with the founding of the International Permanent Commission on Occupational Health, showed that the time was ripe for a new subject to appear on the scene – the occupational health physician – who from then on was to play an important role in the promotion of workers’ health. Conclusions: The article outlines the main features of the Italian industrial transformation at the turn of the new century with special attention focused on Milan, the capital of industry in Italy. It also describes the impact on public opinion caused by the events surrounding the epic construction of the transalpine railway tunnels which began in 1856 with the Mont Cenis tunnel, then the tragic enterprise of the St. Gotthard tunnel in 1883, ending in 1906 with the inauguration of the Simplon tunnel. The Milan congress is examined as well as the developments which, from then on, began increasingly to give physicians specialised in occupational diseases a higher profile in events of an international nature in the defence of workers’ health but also in the interests of economic development. Culle dell’industria e della medicina del lavoro nel mondo moderno: Milano 1906 - Annus Mirabilis Introduzione: Viene esaminato il caso di Milano, la principale città industriale italiana, dove, nel 1906, si tiene L’Esposizione Internazionale che ha rappresentato l’acme di un periodo di accelerata crescita industriale, primo vero atto della rivoluzione industriale in Italia. I 25 anni che intercorrono tra l’Esposizione Industriale Nazionale del 1881, tenutasi sempre a Milano, e l’Esposizione del 1906 rappresentano il periodo cruciale di questo decollo. È proprio in occasione della nuova fase di organizzazione industriale che la Milano della società civile si mostra interessata e sempre di più pone attenzione a ciò che si intende con il termine di “Questione Sociale”. In uno scenario ricco di dibattiti e di scambi di idee ed esperienze con Torino, un’altra delle maggiori città industriali del Nord Italia e culla dell’industria meccanica e dell’automobile, di movimenti sociali, di partiti politici e di organizzazioni sindacali nasce e si sviluppa quello che deve essere considerata la via italiana al welfare del ventesimo secolo. Risultati: Questo è il contesto nel quale si tiene a Milano dal 9 a 14 giugno del 1906 il Congresso Internazionale delle Malattie da Lavoro voluto da Luigi Devoto e Malachia De Cristoforis. Il successo dell’evento avrà come seguito tutta una serie di iniziative della International Permanent Commission on Occupational Health e ciò dimostra che i tempi erano maturi perchè un nuovo soggetto calchi la scena, il medico del lavoro, soggetto che da questo momento avrà un ruolo decisivo per la salute dei lavoratori. Conclusioni: L’articolo vuole mettere in evidenza le caratteristiche più notevoli dello sviluppo industriale italiano verificatosi a cavallo del secolo ponendo particolare attenzione al così detto “Triangolo industriale” delimitato dalle città di Milano, Torino e Genova. Vi si descrive inoltre l’impatto sull’opinione pubblica prodotto dagli eventi che si sviluppano attorno all’epica realizzazione dei trafori alpini iniziati nel 1856 con il tunnel del Moncenisio, continuata con la tragica impresa del San Gottardo nel 1883 e conclusasi nel 1906 con l’inaugurazione del Sempione. Viene infine preso in esame il congresso milanese per le malattie del lavoro a partire dal quale i medici interessati alla salute dei lavoratori avranno sempre più un ruolo importante in eventi nazionali ed internazionali.